Immediate Benefit of Art on Pain and Well-Being in Community-Dwelling Patients with Mild Alzheimer's. (20th January 2020) - Pongan, Elodie; Delphin-Combe, Floriane; Krolak-Salmon, Pierre; Leveque, Yohana; Tillmann, Barbara; Bachelet, Romain; Getenet, Jean-Claude; Auguste, Nicolas; Trombert, Béatrice; Dorey, Jean-Michel; Laurent, Bernard; Rouch, Isabelle
Objective: The present report aims to evaluate whether singing intervention can bring an immediate benefit that is greater than the one provided by painting intervention on pain and well-being. Methods: Fifty-nine mild patients with Alzheimer disease were randomized to a 12-week singing (n = 31) or painting group (n = 28). In the present analysis, the immediate evolution of pain and well-being was compared across sessions between the 2 groups using mixed-effects models. Results: We observed a significant improvement in well-being for both singing and painting groups immediately after sessions, compared to the assessment before the sessions. We did not observe this improvement across the sessions for pain intensity measurement. Discussion: Our results revealed that both painting and singing interventions provide an immediate benefit on the patients' well-being.